Experimental investigation of small-scale clay blocks masonry walls with chases under compression. (1st March 2021) - Simonetti Milani, Alisson; Lübeck, André; Mohamad, Gihad; Barros da Silva Santos Neto, Almir; Budny, Jaelson
Abstract: The clay block structural masonry is the most common building system in Brazil, being used even in buildings with ten or more floors. Sometimes, when the buildings are already in use and the total load is fully completed, the dwellings users need to change hydraulic, gas or electrical installation position in masonry walls, cutting the structural elements. This is the most critical problem for building masonry safety because it was not originally predicted during design. The aim of this study was to evaluate the influence of chases on the mechanical behavior of structural masonry walls under compression using clay blocks small-scale models with proportions of 1:5. Three chase positions and depth were tested, as follows: horizontal, vertical and inclined chases, with depths of 20%, 30% and 50% in relation to masonry thickness. Also, concentric and eccentric loads were considered during tests. From experimental results, it was possible to conclude that the presence of horizontal and inclined chase changed the failure mode characteristics of masonry. For masonry with mid-height horizontal chase, it was found to have a significant drop on the residual strength. From experimental tests, it was possible to obtain a relationship between the strength reduction and the chase depth and load conditions. The strength reduction due to the second-order effects induced by the horizontal chases can be successfully evaluated by normative models, specially EN 1996-1-1.